An Efficient and cost effective maximum clique analysis based approximation in military application of Wireless Sensor Network - Jaigirdar, F. T.; Islam, M. M.; Huq, S. R. (2011 14th International Conference on Computer and Information Technology, 2011)
Military Applications of Wireless Sensor Network in domains of maximizing security and gaining maximum benefits from attacking the opponent is a challenging and prominent area of research now-a-days. A commander's goal in a battle field is not limited by securing his troops and the country but also to deliver proper commands to assault the enemies using the minimum number of resources. In this paper we propose, for the first time, an efficient and low cost approximation algorithm using the maximum clique analysis that finds the strategy of maximizing the destruction, in a battlefield, to defeat the opponents with minimum resources. Experimental results show the effectiveness of the proposed algorithm in the prescribed areas of applications and the impacts of different parameters used on its performance measures.